2007
DOI: 10.1248/jhs.53.215
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Temperature during Irradiation on the Production of 2-Alkylcyclobutanones in Beef

Abstract: Beef patties were irradiated with γ-rays at three temperatures, room temperature, chilled, and frozen. 2-Alkylcyclobutanones in irradiated beef patties were then analyzed to confirm the effects of the three temperatures during irradiation on their production. The production of 2-dodecylcyclobutanone (2-DCB) and 2-tetradecylcyclobutanone (2-TCB) were decreased in the samples cooled with ice and dry ice compared with those at room temperature. 2-DCB was dominant in the samples irradiated at room temperature, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 14 publications
(17 reference statements)
0
3
0
Order By: Relevance
“…Obana et al have reported a similar relationship of DCB and TCB and their precursor fatty acids in irradiated animal meat and salmon 14) ῌ The amounts of DCB and TCB formed on irradiation are sensitive to the temperature during irradiation. The DCB/TCB ratios in frozen beef and pork were about 60῍ lower than those in fresh pork and beef 20), 21) ῌ All the samples in our study were irradiated in the frozen state. Additionally, Stevenson reported that the position of palmitic and stearic acid in triglyceride may influence the quantity of ACBs formed 21) ῌ In pork, palmitic acid tends to bind to position 2 of the glycerol backbone, while stearic acid is most likely to bind to position 1.…”
Section: Analysis Of Irradiated Food According To En1785mentioning
confidence: 63%
See 1 more Smart Citation
“…Obana et al have reported a similar relationship of DCB and TCB and their precursor fatty acids in irradiated animal meat and salmon 14) ῌ The amounts of DCB and TCB formed on irradiation are sensitive to the temperature during irradiation. The DCB/TCB ratios in frozen beef and pork were about 60῍ lower than those in fresh pork and beef 20), 21) ῌ All the samples in our study were irradiated in the frozen state. Additionally, Stevenson reported that the position of palmitic and stearic acid in triglyceride may influence the quantity of ACBs formed 21) ῌ In pork, palmitic acid tends to bind to position 2 of the glycerol backbone, while stearic acid is most likely to bind to position 1.…”
Section: Analysis Of Irradiated Food According To En1785mentioning
confidence: 63%
“…Some studies reported that the amounts of ACBs in food decreased as the irradiation temperature decreased 10)19,20) ῌ For example, the DCB and TCB concentrations in beef irradiated in a frozen state are lower than those in beef irradiated chilled or at room temperature 20) ῌ Therefore, we used foodstu#s irradiated in the frozen state to confirm the ability of EN1785 to detect irradiated food. Table 2 shows the concentrations of DCB and TCB in beef, pork, chicken and salmon unirradiated and irradiated with g-rays (0.5ῌ4 kGy).…”
Section: Analysis Of Irradiated Food According To En1785mentioning
confidence: 94%
“…2-DCB production has also been shown to be lower in irradiated frozen salmon than in chilled All-cis-2-tetradecyl-5 0 ,8 0 ,11 0 -trienylcyclobutanone salmon but there was no difference in 2-TCB levels (Stewart et al, 2000). In a comparison of the effects of irradiation of beef at room temperature, chilled on ice or frozen by dry ice, Obana et al (2007b) showed that the production of both 2-DCB and 2-TCB decreased considerably with lowering of the temperature, but that 2-DCB decreased more (Table 2). When expressed as a molar proportion to the precursor fatty acid the production of 2-DCB and 2-TCB were similar at room temperature but less 2-DCB was produced under cold conditions.…”
Section: Occurrence Of 2-acbsmentioning
confidence: 98%